Feminism and art history: questioning the litany - Broude, Norma; Garrard, Mary D. (Icon editions, 1982)
A long-needed corrective and alternative view of Western art history, these seventeen essays by respected scholars are arranged chronologically and cover every major period from the ANcient 2gypt to the present. While several of the essays deal with major woman artists, the book is essentially about western art history and the extent to which it has been distorted, in every period, by sexual bias. With 306 illustrations.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; Feminism and art; Feminism in art; amérique du nord; amériques; antiquité; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; occident; premier cycle; périodes historiques; régions géographiques; thématiques